About the nature of the main parameters of temperature sensors - Budjak, Jaroslav; Hotra, Oleksandra (Видавництво Національного університету «Львівська політехніка», 2002)
The results of study of the nature of sensor materials properties are given in this paper. For study of the nature of conductivity and other kinetic properties of semiconductor materials modern kinetic theory was used. The theory is based on statistical sum of large nonequilibrium ensemble of charge carrier gas particles in semiconductors.
Keywords: kinetic properties; conductivity; dispersion law; scattering